Arterial supply and morphological characteristics of sympathetic neurons in the human superior cervical ganglion - Boljanović, Jelena; Milisavljević, Milan; Latas, Milan; Puškaš, Laslo; Bogosavljević, Nikola; Vujačić, Marko; Aleksandrić, Dejan; Ćetković, Dejan; Branković, Nemanja; Dožić, Aleksandra; Ćetković, Mila (Frontiers in Neuroanatomy, 2024)
The reason for this investigation was the question of whether within the human superior cervical sympathetic ganglion (SCSG) there is an uneven layout of blood vessel network and of mast cells, which could possibly influence the nerve cells and axons in a specific portion of the ganglion. By means of immunohistochemical staining, we depicted the intraganglionic microvessels as well as mast cells within the SCSG. To our knowledge, there are no reports on the density of microvessels in the human SCSG, on the number of mast cells within the ganglion, or on the number and measurements of ganglionic cells. The intraganglionic network of blood vessels and clusters of ganglionic neurons are uniformly arranged within the SCSG. The intraganglionic mast cells are numerous and uniformly present, possibly with the potential of modulating the function of sympathetic ganglionic cells.